2022
DOI: 10.21608/jnsbu.2022.247769
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Foot Reflexology Technique on Diabetic Neuropathy Patients' Health Outcomes

Abstract: Background: Self-foot reflexology is effective in patients with type 2 diabetes mellitus (T2DM) by reducing symptoms of peripheral neuropathy, as numbness and pain, tingling and stimulate the circulation of blood to the feet directly which help in reducing the loss of sensation to the foot. Aim of study: Was to evaluate effect of foot reflexology technique on diabetic neuropathy patients' health outcomes. Design: A quasi-experimental design will be utilized to achieve the aim of this study. Setting: The study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Based on the results of research by (Gomaa et al, 2022) using Quasiexperimental, it was found that blood glucose levels improved after reflexology intervention for 90%, 87%, 72% & 60% of the patients studied, respectively, compared to the pre-flexology intervention with a significant difference p≤0.01. Research conducted by (Lewen, 2022) used a pre-experiment with one group pretestposttest design.…”
Section: Discussionmentioning
confidence: 98%
“…Based on the results of research by (Gomaa et al, 2022) using Quasiexperimental, it was found that blood glucose levels improved after reflexology intervention for 90%, 87%, 72% & 60% of the patients studied, respectively, compared to the pre-flexology intervention with a significant difference p≤0.01. Research conducted by (Lewen, 2022) used a pre-experiment with one group pretestposttest design.…”
Section: Discussionmentioning
confidence: 98%
“…In the study of Thomas [30], as a result of foot reflexology applied to the groups with different antidiabetic treatment options, it was determined that the glycemic control of the individuals in the intervention group improved compared to the values before the application [30]. In other studies, it has been stated that the application of reflexology reduces blood sugar levels and A1c values in patients with diabetes [39][40][41]. Based on the results of these studies, it can be said that reflexology application for blood sugar control is effective on patients.…”
Section: Discussionmentioning
confidence: 99%